How Can the Foundations of Democracy be Weakened? Case Study of Inaccuracy and Independency of Election Data in Indonesia - Yandra, Alexsander; Faridhi, Adrian; Asnawi, Eddy; Setiawan, Husni; ., Sudaryanto; Yasir, Ilham Muhammad (Journal of Ecohumanism, 2024)
One of the efforts to strengthen democracy in a country is by conducting an honest and fair process of the general election. However, several cases have resulted in a decline in the quality of general and local leader elections with various potential problematic politics, such as the potential for novice voters who are 17 years old or married, relocated, and not being registered as voters. This phenomenon is a problem that has always been an evaluation material for every election organizer, even the KPU (Komisi Pemilihan Umum-General Elections Commission)'s performance has always been a concern regarding this matter. This research was conducted using a qualitative method with a case study approach to uncover this fatal problem. Data were obtained through in-depth interviews with informants and literature related to research issues. This study refers to the case of the voter data updating process by the Riau's KPUD (Komisi Pemilihan Umum Daerah-Regional General Elections Commission), where there were 51,469 ineligible voters (TMS) registered as permanent voters. As a reference for analysis, this study used the theory of democracy and the political rights of voters. The data were processed with an Emic-etic approach to find a complete and in-depth analysis. The results show that the problem of voter inaccuracy occurs due to poor accuracy of the Final Voter List (Daftar Pemilih Tetap-DPT) and lack of transparency in the KPU and Disdukcapil (Dinas Kependudukan dan Catatan Sipil-Department of Population and Civil Registration) systems. In addition, the supply of voter data through the Disdukcapil limits the KPU in accessing population data, resulting in poor voter data updating. This also has implications for a continuous voter data independence strategy to minimize fraud in the general election process and Local Leader Election in the coming period. This study has implications for the DPT strategy recommendation where the KPU should get the authority to use voter data independently ahead of the election with the provisions of implementing a continuous voter registration system well. KPU can make data renewal anytime. The integrity of the foundation of democracy needs to be maintained in running the country to achieve noble ideas and goals.